PENGEMBANGAN MODUL REAKSI KIMIA BERBASIS CIRCULAR ECONOMY MELALUI BIOKONVERSI SAMPAH MENJADI PUPUK ORGANIK CAIR DALAM MENINGKATKAN KESADARAN LINGKUNGAN SISWA - Gina Salsabila; Meirita Sari; Khairiah Khairiah (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
Increasingly complex environmental issues demand the involvement of the educational world in shaping students' awareness and sustainable behavior through science learning that is relevant to real-life contexts. This study aims to produce a circular economy-based learning module on the content of chemical reactions through the bioconversion of organic waste into liquid organic fertilizer to increase environmental awareness of students at SMP IT Khairunnas, Bengkulu City. The approach used is Research and Development (R&D) with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects involved 30 ninth-grade students and a science teacher. Data collection was carried out through observation, interviews, and questionnaires with instruments in the form of expert validation sheets, student response questionnaires, and teacher observation sheets. Data analysis was carried out descriptively quantitatively and qualitatively to determine the level of feasibility and effectiveness of the developed product. The results showed that the module obtained a validation score of 82.76% from content experts, 79.21% from presentation experts, and 89.63% from language experts with a very feasible category, student responses to the practicality of the module were 73.06% and 92% from teacher responses. The effectiveness of the module is demonstrated by the improvement in student learning outcomes, with an average pretest score of 65.43 and a posttest score of 86.23, and an N-Gain score of 0.61. In addition, the questionnaire results showed a level of student environmental awareness of 86%, and observation results showed a level of student psychomotor skills of 89%, both of which are in the very good category. The circular economy-based module effectively increases environmental awareness because it presents the concept of chemical reactions through direct experience of organic waste bioconversion, so that students are able to understand the relationship between scientific processes, waste management, and environmental sustainability.